Improving Wigner-Hough Transform for Hardware Implementation to Intercept LFMCW Signals - Guner, Kani K.; Erkmen, Burcu; Gulum, Taylan O.; Erdogan, A. Yasin; Yildirim, Tulay; Durak Ata, Lutfiye (IEEE, 2015)
Linear Frequency Modulated Continuous Waveform is generally used in Low Probability of Intercept radars. In studies to intercept this waveform with Wigner-Hough Transform based methods at low SNR (-8dB and below) values it is an important design criteria to obtain the resulting performance with less computation density. The decrease in computation density will provide the use of fewer resources in hardware implementation and less delay to obtain results. In this study; effects of sample and hold type intermediate sampling on Wigner Hough Transformation are examined and it is intended to reduce the complexity by means of the proposed columnar thresholding method. Using the simulated signal database, the Probability of Detection and the Probality of Chirp Rate Estimation are calculated for proposed and alternative methods, then performance for low SNR values are compared.
Keywords: LPI; FMCW; Wigner-Hough Transform; Columnar Thresholding; DISCRETE-TIME; Engineering; Telecommunications